(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The rise of digital technologies and internet access has transformed commerce by connecting buyers and sellers more effectively. In India, e-commerce has become a key driver of economic growth, supported by smartphone adoption, digital payments, and wider internet penetration across urban and rural areas. This paper reviews the benefits, challenges, and future prospects of e-commerce in the Indian market. While advantages such as 24/7 accessibility, cost efficiency, and consumer convenience make online shopping increasingly attractive, barriers like cybersecurity risks, logistical hurdles, counterfeit products, and regulatory pressures limit its growth. The study also highlights major e-commerce models (B2B, B2C, C2C, C2B, B2A, C2A) and recent market trends. Despite existing challenges, India’s digital economy shows strong potential, driven by innovation, policy support, and investor interest. E-commerce is thus set to remain a crucial force in reshaping India’s retail and economic landscape.